Distribution and impact of the Argentine ant, Linepithema humile (Mayr), in South Africa - Luruli, Ndivhuwo Mord (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2007.